AN ANALYSIS OF LOVE IN MATTHEW LOGELIN’S NOVEL “TWO KISSES FOR MADDY” - Taufik, Muhammad; B, Mukarramah (Elite : English and Literature Journal, 2017)
Abstract This writing studied about analysis of love in Two Kisses for Maddy novel by Matthew Logelin.  The aim of this study is to find out the kinds of love and meaning of love in “Two Kisses for Maddy” novel by Matthew Logelin. The writer used descriptive qualitative method and structuralism approach in analyzing the kinds of love and meaning of love in the novel. In this study, the instrument that used by the writer was note taking. From the result, the writer found out that there are four kinds of love that contain maternal love, thirteen kinds of love that contain paternal love and nine kinds of love that contain love between husband and wife. And then the writer found the meaning of love in the novel. The implication of this study is to inform the public that a novel is not only use full as a reading at leisure or entertainment, but the novel can also be functioning as knowledge of love. Hopefully, this thesis can contribute to education as an analysis of literary work, especially for students of English and Literature Department.Abstrak                                                                                                                         Analisa Cinta dalam Novel Karya Matthew Logelin “Two Kisses For Maddy”. Tulisan ini merupakan penelitian yang menganalisa cinta dalam novel “Two Kisses for Maddy” karya Matthew Logelin. Tujuan penelitian ini adalah untuk mengetahui jenis-jenis cinta dan makna cinta yang terkandung dalam novel “Two Kisses for Maddy” karya Matthew Logelin. Penulis menggunakan metode kualitatif deskriptif dengan pendekatan strukturalisme dalam menganalisa jenis-jenis cinta dan makna cinta yang terkandung dalam novel. Instrumen yang digunakan adalah note taking. Dari hasil analisa, penulis menemukan tiga jenis cinta, yaitu 4 data mengandung cinta ibu, 13 data mengandung cinta ayah, dan 9 data yang mengandung cinta antara suami istri. Dan kemudian terdapat makna yang terkandung pada masing-masing jenis cinta yang ditemukan. Tulisan ini diharapkan dapat menginformasikan kepada masyarakat bahwa novel bukan hanya digunakan sebagai bacaan waktu senggang, namun juga dapat berfungsi sebagai pemberi pengetahuan tentang segala hal termasuk tentang cinta. Kemudian juga diharapkan tulisan ini dapat member kontribusi pada pendidikan khususnya dalam menganalisa karya sastra, khususnya untuk mahasiswa jurusan Bahasa dan Sastra Inggris.